THE IMPACT OF BIO-FUNGICIDES, GROWTH STIMULATORS AND THEIR COMBINATIONS ON SUNFLOWER WATER INTAKE UNDER NON-IRRIGATED CONDITIONS OF THE STEPPE ZONE - Domaratskyi , Ye.O; Kozlova , O.P.; Domaratskiy, O.O.; Kaplina, A.I.; Koruniak , O.P. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The study examines the impact of complex application of fungicides and growth stimulators of biological origin on sunflower water intake and rational use of moisture by the plants. The experimental research was conducted under conditions of the research field of Kherson State Agrarian University on dark chestnut alkaline soil containing 2.5% of humus in the plow layer. In 2016 – 2018 the field experiment was carried out by a three-factor scheme, where Factor A – environmentally friendly preparations and their combinations (Fitosporyn; Fito Help; Fitosporyn / Hart Super; Fito Help / Hart Super; a test variant – without treatment); Factor В – sunflower hybrids of the company «LG» (Tunca and LG 5580); Factor С – different stages of using preparations (seed treatment a day before sowing and vegetation treatment of the plants at the budding stage). The plots were located by a split-block method. All the necessary evaluations, records and observations were performed according to the generally accepted methods of the state variety trials, and specific methods were also employed - field, analytical, calculative-comparative and the method of mathematical and statistical processing of experimental data.The research results made it possible to determine that the coefficient of water intake tended to decrease under the influence of the preparations under study, especially when calculated per the seed yield. In comparison with the test variant, better variants with complex application of the preparations reduced the coefficient of water intake by 20 – 21% that proves essential water saving for the formation of a unit of the main products. The calculation of the coefficient of water intake per dry biomass showed that it was almost unchangeable by all the research variants.